EFEKTIVITAS AIR REBUSAN SIMPLISIA DAUN BINAHONG (ANREDERA CORDIFOLIA) TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI BPM BERTHA - Siagian, Nurul Aini; Yanti, Mutiara Dwi; Harahap, Maharani Syahputri (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
During the immediate postpartum period, starting right after placenta delivery and typically lasting around 40 days until the reproductive organs return to their pre-pregnancy state, the binahong plant (Anredera cordifolia Steenis) is widely utilized in traditional herbal medicine. Renowned for its medicinal properties found in its tubers, stems, flowers, and leaves, this study aimed to assess how effective binahong leaf decoction (Anredera Cordifolia) is in facilitating the healing of perineal wounds in postpartum women treated at the Bertha Clinic. Using a quasi-experimental design—specifically, a Posttest Only Control Group Design—the research involved a sample of 20 third-trimester pregnant women selected through total sampling in March. Bivariate analysis using the t-test yielded significant results (p=0.002, p<0.05), confirming the efficacy of binahong leaf decoction in promoting perineal wound healing among postpartum women attending Pratama Bertha Clinic.